2010
DOI: 10.1111/j.1748-5967.2010.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auditory stimuli on the lifespan of Drosophila melanogaster

Abstract: It is well known that music can have calming effects on humans, other mammals and birds. Reducing environmental stress or enhancing the resistance to certain stressors has been shown to extend lifespan in several organisms. Evidence also suggests that mild temporary stress may also enhance stress resistance and ultimately slow the aging process. This study explored the possibility that music may influence the lifespan of the fruit fly Drosophila melanogaster, possibly by affecting responses to stress. Flies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The radiofrequency interference on physio-biochemical process of insects was also reported by Nelson (1996), who elaborated that radiofrequency can affect the nervous systems which control endocrine system and other systems cause unexpected functions such as inhibiting the formation of protein vitellin and juvenile hormone that control the growth and differentiation of insects. In this study, we found that radiofrequency negatively affected the adult performance such as longevity and weight of adult M. vitrata, findings are line with that of Morales et al (2010), who reported the reduction of lifespan when exposed to classical music in the Drosophila melanogaster. Chen et al (2013) reported that acoustic frequency had significant impact on the lifespan and increased the mortality rate of Tetradcus citri.…”
Section: Sex Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…The radiofrequency interference on physio-biochemical process of insects was also reported by Nelson (1996), who elaborated that radiofrequency can affect the nervous systems which control endocrine system and other systems cause unexpected functions such as inhibiting the formation of protein vitellin and juvenile hormone that control the growth and differentiation of insects. In this study, we found that radiofrequency negatively affected the adult performance such as longevity and weight of adult M. vitrata, findings are line with that of Morales et al (2010), who reported the reduction of lifespan when exposed to classical music in the Drosophila melanogaster. Chen et al (2013) reported that acoustic frequency had significant impact on the lifespan and increased the mortality rate of Tetradcus citri.…”
Section: Sex Ratiosupporting
confidence: 90%
“…In this study, we found that radiofrequency negatively affected the adult performance such as longevity and weight of adult M. vitrata , findings are line with that of Morales et al . (), who reported the reduction of lifespan when exposed to classical music in the Drosophila melanogaster . Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…The speed of sound depends on the medium the waves pass through, and is a fundamental property of the material ( McCall, 2010 ). Living organisms produce and perceive sound to help understand the environment around them ( Morales et al, 2010 ; Aggio et al, 2012 ). Sound-based communication through the eardrum or specialized mechanosensory systems are commonly found in humans and certain terrestrial mammals ( Grothe et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies about the potential effects of sound have focused on vertebrates, however, several studies have dealt with those of insects. Those are exemplified from significantly reduced female calling and mating in response to ultrasonic stimuli in the Indian meal moth, Plodia interpuntella (Huang & Subramanyam 2004), suppression of sex pheromone behavior by ultrasonic stimuli in the gypsy moth, Lymantia dispar (Baker & Cardé 1978), and reduction of lifespan when exposed to classical music in the fruit fly, Drosophila melanogaster (Morales et al 2010).…”
Section: Introductionmentioning
confidence: 99%